Comparative Evaluation of the Antidiabetic Effect of Flavonoids Dihydroquercetin and Thamiflaside - Kuchkarova, Lubov; Kayumov, Khasan; Eshbakova, Komila; Agzamova, Manzura; Karimova, Irodakhon; Berdiyarova, Sevara; Abdurakhmonov, Jakhongir; Achilov, Rashidbek; Gayibov, Ulugbek; Ergashev, Nurali (Trends in Sciences, 2025)
Diabetes mellitus (DM) is a major global health burden, ranking among the top three diseases leading to disability and mortality. Although some flavonoids exhibit antidiabetic properties, the effects of many remain insufficiently explored. This study investigates the potential of 2 flavonoids—dihydroquercetin (DHQ) and thamiflaside (TF)—to mitigate alloxan-induced diabetes in rats, thereby addressing an important gap in current knowledge. Male rats were divided into 4 groups: Negative control, diabetic (positive control), and two treatment groups receiving either DHQ or TF (30 mg/kg/day, per os) following alloxan induction (50 mg/kg/day, intraperitoneally for 3 days). Alloxan administration resulted in significant hyperglycemia, polydipsia, polyuria, and elevated levels of serum glucose, triglycerides, cholesterol, α-amylase, ALT, and AST, as well as increased maltase and sucrase activity in the small intestinal mucosa. Conversely, levels of insulin, total protein, alkaline phosphatase, and glutathione peroxidase were significantly reduced. DHQ treatment led to marked improvements in fluid balance, glycemic control, lipid profile, enzyme activity in serum, and disaccharidase activity in the intestinal mucosa. Notably, DHQ showed a stronger corrective effect than TF across most parameters. These findings highlight DHQ as a promising candidate for the treatment of diabetes and its associated metabolic disturbances, while also supporting TF as a potential alternative. HIGHLIGHTS Dihydroquercetin (DHQ) and thamiflaside (TF) were tested in alloxan-induced diabetic rats. Alloxan caused hyperglycemia, dyslipidemia, enzyme imbalance, and intestinal disruption. DHQ improved glycemic control, lipid profile, and restored enzymatic activities. TF showed partial correction but weaker efficacy compared to DHQ. DHQ emerges as a stronger candidate for managing diabetes-related metabolic disorders. GRAPHICAL ABSTRACT